2002
DOI: 10.1212/wnl.59.1.132
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind placebo-controlled trial of topiramate treatment for essential tremor

Abstract: The safety and efficacy of topiramate (400 mg/d or maximum tolerated dose) as monotherapy or adjunctive treatment of essential tremor were investigated in a placebo-controlled, crossover study (n = 24). Topiramate resulted in significantly greater reductions from baseline based on normalized scores for a clinical rating of tremor location/severity, specific motor tasks/functional disabilities, and tremor-resultant functional disabilities. Most common adverse events were appetite suppression/weight loss and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(59 citation statements)
references
References 8 publications
0
57
0
2
Order By: Relevance
“…Four relevant studies [50][51][52][53] assessed the effect of topiramate in limb tremor, providing evidence for therapeutic benefit [50][51][52][53]. A placebo-controlled cross-over study in 24 patients using up to 400 mg/d as mono-or adjunct therapy [51] found a significant reduction of tremor subscores. In a subsequent article [53], the same authors report combined results of 3 randomized, double-blind, placebo-controlled, cross-over trials of topiramate for ET (maximum tolerated dose of up to 400 mg/d) in adult patients observed for 10 weeks per treatment arm (active drug then placebo vs placebo then active drug).…”
Section: Topiramatementioning
confidence: 99%
“…Four relevant studies [50][51][52][53] assessed the effect of topiramate in limb tremor, providing evidence for therapeutic benefit [50][51][52][53]. A placebo-controlled cross-over study in 24 patients using up to 400 mg/d as mono-or adjunct therapy [51] found a significant reduction of tremor subscores. In a subsequent article [53], the same authors report combined results of 3 randomized, double-blind, placebo-controlled, cross-over trials of topiramate for ET (maximum tolerated dose of up to 400 mg/d) in adult patients observed for 10 weeks per treatment arm (active drug then placebo vs placebo then active drug).…”
Section: Topiramatementioning
confidence: 99%
“…Although its mechanisms of action have not been fully elucidated, TPM is known to enhance the activity of g-aminobutyric acid (GABA) through interaction with GABA A receptors, as well as to block voltage-dependent sodium channels and kainate/ [alpha]-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) glutamate receptors (Schneiderman, 1998). Emerging evidence indicates that TPM might offer promising applications for the therapy of other neurological conditions, such as neuropathic pain and essential tremor (Chong and Libretto, 2003;Connor, 2002), as well as several psychiatric disorders, such as bipolar disorder (Calabrese et al, 2001;Grunze et al, 2001), schizoaffective disorder (Deutsch et al, 2003), posttraumatic disorder (Berlant and Van Kammen, 2002), Tourette's syndrome (Abuzzahab and Brown, 2001) and some clusters of schizophrenia (Drapalski et al, 2001). The therapeutic potential of TPM for these disorders, however, is disputed on account of contrasting findings (Arnone, 2005;Millson et al, 2002) and in view of its numerous cognitive and affective side effects, such as depression, hallucinosis and cognitive deterioration (Matthews and Miller, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Topiramate is an anticonvulsant that blocks sodium channels and potentiates GABA activity. Three class II studies [25][26][27] and one class IV study 28 found that topiramate in doses up to 400 mg/day reduced tremor. One double-blind, placebo-controlled trial 28 in 62 patients with ET reported an 18% to 23% improvement in clinical rating scales with topiramate use, compared to 0 to 1% in patients taking placebo.…”
mentioning
confidence: 99%